p53: an overview of over two decades of study - Cheah, Phaik Leng; Looi, Lai Meng (College of Pathologists, Academy of Medicine Malaysia, 2001)
p53 is the most commonly mutated gene in human cancers. It encodes a 53 kilodalton protein with several evolutionarily conserved domains viz sequence-specific DNA binding, tetramerisation, SH3 molecule binding, C-terminal and N-terminal. Existing in the cell at a very low level and in a relatively inactive form, p53 protein is increased and activated during periods of cellular stress. Unlike other proteins, the increase in protein level and its activation result from modification of the protein rather than genetic transcriptional or translational upregulation. Normally, Mdm2 protein interacts with p53 protein and effectively targets it for ubiquitin proteolysis within an autoregulatory feedback loop. Phosphorylation at the N-terminus reduces p53 interaction with Mdm2 with a resultant increase in p53 protein level. Modification at the C and N termini via phosphorylation or acetylation upregulates binding to specific DNA targets increasing transcription of these downstream genes. The net effect of p53 protein increase and activation lies in arrest of the cell in cycle which allows time for repair of the incurred damage or apoptosis or death of the cell. Failure of these normal protective and adaptive mechanisms caused by mutation of the p53 gene with product of an abnormal protein, loss of p53 protein through interaction with and degradation by HPV E6 protein or overexpressed Mdm2 etc. permits DNA-damaged cells to continue replicating. Left unchecked, this frequently contributes to tumourigenesis. Various methods have been devised to screen for mutations of the p53 gene, still the most common source of failed p53 mechanism. These include immunohistochemical detection of mutated proteins or identification of altered electrophoretic mobility of mutated p53 sequences. Sequencing of the gene nonetheless remains the most accurate method for determination of mutation. Major advances have been made in p53 research but the most meaningful probably lies in the promising results achieved in tumour therapy where introduction of wild type p53 gene has resulted in regression of non-small-cell lung cancer (NSCLC). Many other notable developments in this field include description of p53 homologues, "gain of function" mutants, p53 polymorphisms, angiogenesis-inhibiting properties of wild type p53 protein etc.